Development of a Novel Pt3V Alloy Electrocatalyst for Highly Efficient and Durable Industrial Hydrogen Evolution Reaction in Acid Environment. Issue 16 (14th March 2023) - Da, Yumin; Jiang, Rui; Tian, Zhangliu; Chen, Ganwen; Xiao, Yukun; Zhang, Jinfeng; Xi, Shibo; Deng, Yida; Chen, Wei; Han, Xiaopeng; Hu, Wenbin
Abstract: Alloying platinum with early transition metals is a promising approach to optimize the adsorption behaviors of catalysts. Nevertheless, the large negative redox potential between early transition metals and Pt hinders the fabrication of such alloys. Herein, a strategy combining the thermal shock technique with electrochemical activation to prepare Pt3 V alloy as a hydrogen evolution reaction catalyst is reported for the first time. Electrochemical tests show that the as‐prepared catalyst exhibits exceptional catalytic activity and durability in 0.5 m H2 SO4, surpassing the state‐of‐the‐art 20 wt.% Pt/C. The catalyst can maintain its activity after 100 h tests without evident decay under the current density of 500 mA cm −2 . Theoretical calculations demonstrate that the optimized hydrogen absorption and high vacancy formation energy of Pt3 V contributes to the enhanced electrocatalytic activity and stability. This work may spur future research for other Pt‐based early transition metal alloy catalysts for electrocatalysis. Abstract : Pt3 V alloy is synthesized with a thermal shock technique followed by the electrochemical activation method for the first time. The hydrogen evolution reaction activity is superior to 20 wt.% Pt/C in both acidic and basic conditions. The superior activity and stability originate from the optimized hydrogen adsorption ability and high vacancy formation energy.